Dynamic response analysis of story-adding structure with isolation technique subjected to near-fault pulse-like ground motions - Ma, XiaoTong; Bao, Chao; Doh, Shu Ing; Liu, HaiFeng; Zhang, L. X.; Ma, Z. W.; He, Y. (2021)
The isolation technique is widely studied and applied in structural engineering due to its excellent seismic performance. However, the existing research mostly focuses on the conventional structure under the action of regular ground motions. In this paper, a story adding seismic structure, a base-isolated structure, and a story-adding isolated structure were simulated by using numerical simulation methods. The dynamic response characteristics of the three structures under near-fault pulse-like ground motions are analysed and compared with the far-fault ground motions. The results showed that using the base isolation can significantly extend the period of the main structure and reduce the seismic response on the upper structure. The inter-story drift ratio, inter-story shear force, and the story acceleration of all three structures under near-field pulse-like ground motions were all larger than that of far-field earthquakes. Both base-isolated structure and story-adding isolated structure showed excellent damping performance. Besides, the damping properties of the base-isolated structure are better than the story-adding isolated structure.